2017
DOI: 10.14302/issn.2374-9431.jbd-17-1465
|View full text |Cite
|
Sign up to set email alerts
|

Biopsychosocial Path Model Of Self-management And Quality Of Life In Patients With Type 2 Diabetes

Abstract: Objectives: The present study investigated biopsychosocial predictors (HbA1c, self-efficacy, and social support) of self-management and health-related quality of life among patients with type 2 diabetes. Conclusions:The results confirmed the theoretical model and scientific evidence for providing psychological solution to promote quality of life in patients with type 2 Diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 21 publications
1
3
0
Order By: Relevance
“…This study also indicated that changes in adaptive coping were able to moderate the magnitude of the relationship between illness perceptions and QoL changes. The finding that coping response plays a moderating role in QoL is a new finding for the injury population; however, a similar finding was previously reported among the chronic illness population (Bazzazian et al, 2010). This finding introduces additional implications: if a clinician can increase the use of adaptive coping strategies, this change could weaken the effects of negative illness perceptions on QoL and strengthen the effects of positive illness perceptions on QoL among EI patients.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…This study also indicated that changes in adaptive coping were able to moderate the magnitude of the relationship between illness perceptions and QoL changes. The finding that coping response plays a moderating role in QoL is a new finding for the injury population; however, a similar finding was previously reported among the chronic illness population (Bazzazian et al, 2010). This finding introduces additional implications: if a clinician can increase the use of adaptive coping strategies, this change could weaken the effects of negative illness perceptions on QoL and strengthen the effects of positive illness perceptions on QoL among EI patients.…”
Section: Discussionsupporting
confidence: 61%
“…Although these past studies have shown that illness perceptions and coping had predictive effects on postinjury QoL, the evidence presented was not sufficient to explain QoL changes. Additionally, previous studies have indicated that interactions between illness perceptions and coping responses could significantly explain health outcomes (Bazzazian et al, 2010). Evidence has shown that illness perceptions and coping are associated with QoL; however, little is known about their longitudinal associations.…”
Section: Introductionmentioning
confidence: 99%
“…It is shown that 95% of the diabetes care and treatment among adults are done by the patients themselves (self-care), none of modern diabetes management tools will be effective unless the psychological problems and issues of these patients are solved. 9 This chronic disease can affect a variety of physical functions, as well as mental/psychological condition, interpersonal, familial, and social relationships, and the person's general perception of health. 10 Due to having high burden of disease, frequent complications, direct and indirect financial burdens on the health system, and huge impact of patient's quality of life, diabetes is an important health issue.…”
mentioning
confidence: 99%
“…The research tools included the Broadbent Illness Perception Questionnaire (BIPQ), Multidimensional Body-Self Relations Questionnaire (MBSRQ), and Fear of Cancer Recurrence Inventory Questionnaire (FCRIQ). In past studies, the validity and reliability of BIPQ (23,24), MBSRQ (25)(26)(27), and FCRIQ (28) have been approved. Finally, SPSS software Version 25 was used to analyze raw data using mixed analysis of variance with repeated measures at a significance level (α = 0.05).…”
Section: Methodsmentioning
confidence: 99%